2009
DOI: 10.1017/s0029665109001384
|View full text |Cite
|
Sign up to set email alerts
|

Symposium 4: Hot topics in parenteral nutrition A review of the use of glutamine supplementation in the nutritional support of patients undergoing bone-marrow transplantation and traditional cancer therapy

Abstract: The relationship between glutamine and malignancy can be traced back to the 1950s and the requirement for glutamine for malignant-cell growth in culture. Later studies demonstrated an association between the rate of proliferation of the malignant cells and glutamine usage. The excessive use of glutamine by malignant cells was seen as an opportunity for the development of a treatment using glutamine analogues, but unfortunately excessive toxicity was observed during clinical studies. In animal models glutamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
(88 reference statements)
0
5
0
1
Order By: Relevance
“…43 Previous studies on the use of AlaGln supplementation in parenteral infusion regimens have provided data on systemic outcome parameters in patients in a hypercatabolic or hypermetabolic state or both that might also be relevant in the setting of PD. 35,[44][45][46][47] Given this clinical evidence and considering the adequate peritoneal absorption, it was not unexpected that AlaGln added to PDF also showed systemic effects in PD patients. Accordingly, we found a lower IL-8 concentration and a trend to lower hs-CRP concentrations during treatment with AlaGln compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…43 Previous studies on the use of AlaGln supplementation in parenteral infusion regimens have provided data on systemic outcome parameters in patients in a hypercatabolic or hypermetabolic state or both that might also be relevant in the setting of PD. 35,[44][45][46][47] Given this clinical evidence and considering the adequate peritoneal absorption, it was not unexpected that AlaGln added to PDF also showed systemic effects in PD patients. Accordingly, we found a lower IL-8 concentration and a trend to lower hs-CRP concentrations during treatment with AlaGln compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…23 A possible trend in the objective reduction of mucositis by glutamine supplementation in non-BMT patients receiving chemotherapy and/or radiotherapy has been reported. 37 Furthermore, a Japanese study 38 using a combination of GLN, fibre and oligosaccharides (GFO) was the first retrospective comparative clinical study of mucosal injury in allogeneic HSCT using GFO. Iyama et al concluded that GFO supplementation was an effective supportive therapy to decrease the severity of mucosal injury in HSCT.…”
Section: 12mentioning
confidence: 99%
“…Aunque hay estudios con resultados alentadores y recomendaciones de expertos 46 , la controversia respecto de su utilidad y seguridad continúa 42,47,48 . Recientemente fue publicado un metaanálisis respecto del uso glutamina suplementaria en quimioterapia no asociada a trasplante de médu-la osea 49 . Este trabajo no presenta las fortalezas metodológicas mencionadas más arriba: la bús-queda se describe escuetamente como "una breve búsqueda en Pubmed", no hay revisión explícita ni independiente de la calidad de los trabajos originales y uno de ellos fue eliminado del análisis por defi ciencias metodológicas que no están descritas.…”
Section: Glutamina Suplementariaunclassified